STUDIES ON ORGANOLEPTIC QUALITIES OF ORANGE BASED BLENDED READY-TO-SERVE (RTS) BEVERAGES - RAJESH GUPTA; MANOJ MALAV; N. K. KUSHWAHA; ANKIT PANDEY (The Bioscan, 2015)
Organoleptic changes in orange based blended ready-to-serve (RTS) beverages were studied during its storage. The present study was comprised of two level of preservative (750 ppm and 500 ppm KMS), three level of recipe (orange, pomegranate, aonla and ginger juice) and two blending ratio (90:10:0, 86:10:4). These experiments have nine treatment combinations viz., T-0 (control, 100% orange juice with 750 ppm KMS), T-1(Orange-aonla-ginger (90:10:0) with 750 ppm KMS), T-2(Orange- aonla-ginger (86:10:4) with 750 ppm KMS), T-3 (Orange-pomegranate- ginger (90:10:0) with 750 ppm KMS), T-4 (Orange-pomegranate-ginger (86:10:4) with 750 ppm KMS), T-5 (Orange-aonla-ginger (90:10:0) with 500 ppm KMS), T-6 (Orange-aonla-ginger (86:10:4) with 500 ppm KMS), T- 7(Orange-pomegranate-ginger (90:10:0) with 500 ppm KMS), T-8(Orange-pomegranate-ginger (86:10:4) with 500 ppm KMS). The different organoleptic characteristics viz., colour, taste, flavor and overall acceptability were recorded at 30 days interval upto 90 days. Among the tested treatments with regard to the organoleptic characteristics, the treatment T-4 obtained maximum sensory scores viz., colour (7.33), flavor (8.87), taste (8.99) and overall acceptability (7.67) throughout the storage period.